Dissonant Memories - Fragmented Present : Exchanging Young Discourses between Israel and Germany - Misselwitz, Charlotte; Siebeck, Cornelia (Kultur und soziale Praxis, 2015)
How do young Israelis and Germans communicate about National Socialism and the Holocaust? In this collection of essays, authors from both societies elaborate on the past, their present and, respectively, their identity. They ponder various switches of track through German-Israeli exchange as well as social and political realities in both countries. By highlighting marginalised memories such as Palestinian and migrant ones, they challenge monolithic national memory discourses. Altogether, a trans-national memory discourse emerges - albeit a dissonant and highly subjective one, truthfully reflecting some of the fragmentations that actually exist in both societies.